Management Effectiveness of Village Owned Enterprises in Cigalontang Village Cigalontang Sub District Tasikmalaya District - Dandan Haryono; Agusta Sri Astuti; Yuda Brahmantiar (LAFADZ JAYA Publisher, 2023)
Based on an observation result in Cigalontang Village Cigalontang Sub district Tasikmalaya District it was found that some issues such as Village Owned Enterprises of Cigalontang Village was not right in choosing type of business and did not achieve the objectives of establishing Village Owned Enterprises of Cigalontang Village. Furthermore, the writers formulated a problem “How is the Management Effectiveness of Village Owned Enterprises of Cigalontang Village in Cigalontang Village Cigalontang Sub district Tasikmalaya District?” The objectitive of this research was to determine and to describe the the Management Effectiveness of Village Owned Enterprises of Cigalontang Village in Cigalontang Village Cigalontang Sub district Tasikmalaya District. Theory applied in this research was effectiveness theory analyzed based on effectiveness measures, they are program understanding, right on target, timeliness, goal achievement and real change (Sutrisno, 2010:125-126). This research applied descriptive research method with qualitative approach. Techniques of data collection used were interview, observation and documentation study. Based on research results and discussion, the writers may conclude that the Management Effectiveness of Village Owned Enterprises of Cigalontang Village in Cigalontang Village Cigalontang Sub district Tasikmalaya District has not been effective yet. From five of effectiveness scope dimensions, three dimensions have not been applied well, they are right on target, goal achievement and real change while two effectiveness measures applied well were effectiveness measures in program understanding and timeliness ones.